Effectiveness of applying auricular acupressure to treat insomnia: a systematic review and meta-analysis - Jun, Li; Xiong, Li; Wen, Yu; Yongxiang, Wang (Frontiers in Sleep, 2024)
Insomnia affects quality of life of a significant number of individuals worldwide. Despite the fact that pharmaceutical sleep treatments have shown brief enhancements in sleep quality, these are still not recommended for the long term management of sleep issues. To deal with this problem, our study aims to assess the effectiveness of auricular acupressure to treat insomnia by conducting a systematic review and meta-analysis.Data from randomized controlled trials (RCTs) of auricular acupressure for insomnia was collected from five English-language databases (Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, AMED, and CINAHL) and four Chinese databases (CBM, CNKI, CQVIP, and Wanfang). Relevant data was extracted by two reviewers. I2 statistics was adopted to appraise heterogeneity. The network meta-analysis was applied to compare the effect of auricular acupressure with other methods.Twenty-three randomized controlled trials (RCTs) were included, involving a total of 1,689 patients. The results demonstrated a significant decrease in the PSQI score for the intervention group compared to the control group (SMD = -1.30, 95% CI (-1.65 to -0.96), I2 = 90%). Furthermore, the group receiving auricular acupressure in addition to usual care showed a lower PSQI score compared to the usual care group (SMD = -1.13, 95% CI (-1.33 to -0.93), I2 = 23%). Auricular acupressure was found to enhance the effectiveness of estazolam in improving PSQI score, with the combination of auricular acupressure and estazolam resulting in a lower PSQI score (MD = -4.8, 95% CI (-7.4, -2.1)). Importantly, no serious adverse events were reported. In patients with insomnia following stroke, the intervention group (which received auricular acupressure) exhibited a lower PSQI score compared to the control group (SMD = -0.74, 95% CI (-1.03 to -0.46), I2 = 0%). Similarly, in patients with insomnia related to cancer, the intervention group (receiving auricular acupressure) demonstrated a lower PSQI score compared to the control group (SMD = -0.99, 95% CI (-1.37 to -0.61), I2 = 0%).The effects of auricular acupressure on insomnia are comparable to those of estazolam. Furthermore, auricular acupressure can serve as a complementary treatment to estazolam or other interventions, effectively improving symptoms of insomnia.